2015
DOI: 10.1590/0037-8682-0152-2014
|View full text |Cite
|
Sign up to set email alerts
|

Detection of bla KPC-2 in Proteus mirabilis in Brazil

Abstract: Introduction:Infections caused by Klebsiella pneumoniae carbapenemase (KPC)-producing isolates pose a major worldwide public health problem today. Methods: A carbapenem-resistant Proteus mirabilis clinical isolate was investigated for plasmid profi les and the occurrence of β-lactamase genes. Results: The isolate exhibited resistance to ertapenem and imipenem and was susceptible to meropenem, polymyxin, and tigecycline. Five plasmids were identifi ed in this isolate. DNA sequencing analysis revealed the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…Further, the authors found that the bla KPC gene was detected in 80 % of the isolates, corroborating the data in this study, where we found an occurrence of 88.8 % for the bla KPC gene. These occurrence rates of the bla KPC gene identified in this study highlight the persistence of this gene in K. pneumoniae, and since its detection in 2006 from Recife, Brazil 13 , it remains the main carbapenemase associated with carbapenem-resistant K. pneumoniae samples in several Brazilian states, including Recife-PE 1,5,32 .…”
Section: Discussionsupporting
confidence: 56%
“…Further, the authors found that the bla KPC gene was detected in 80 % of the isolates, corroborating the data in this study, where we found an occurrence of 88.8 % for the bla KPC gene. These occurrence rates of the bla KPC gene identified in this study highlight the persistence of this gene in K. pneumoniae, and since its detection in 2006 from Recife, Brazil 13 , it remains the main carbapenemase associated with carbapenem-resistant K. pneumoniae samples in several Brazilian states, including Recife-PE 1,5,32 .…”
Section: Discussionsupporting
confidence: 56%
“…However, studies have shown that P. mirabilis-CR strains are versatile in terms of carbapenemase production, MBL-NDM, VIMand IMP, 8,[34][35][36] or KPC-producing strains being frequently reported. 6,7,9 With regards to the P. rettgeri strain, this was confirmed to be MBL-NDM type. In general, these strains are rarely described in the literature and there are only a few studies conducted on larger groups.…”
Section: Discussionmentioning
confidence: 74%
“…5 The enzymes responsible for Proteeae resistance to carbapenems, which is considered to be of high epidemiological and clinical significance, are KPC, OXA-48 and NDM, VIM and IMP metallo-β-lactamases (MBL). [6][7][8][9][10][11][12][13] KPC is active on the classes of penicillins, cephalosporins, β-lactamase inhibitors and also on carbapenems and aztreonam, its activity being moderately inhibited by clavulanic acid. 3 MBLs have a significant hydrolytic activity on carbapenems, but without any effect on aztreonam, which they cannot hydrolyze.…”
Section: Introductionmentioning
confidence: 99%
“…Out of 15 imipenem resistant Proteus spp., 20% isolates were positive for blaKPC gene. Single blaKPC-2 positive P. mirabilis was reported in the studies of Pilato et al (2016) and Cabral et al (2014), respectively.11,12 Possibility of this gene transmission may be due to horizontal transmission by transposons, the mobile genetic elements which can transfer from one bacterium to another. 13 Till now only a few numbers of NDM-1 producing P. mirabilis has been detected in di erent studies).…”
Section: Discussionmentioning
confidence: 99%